2019
DOI: 10.1186/s13089-019-0145-4
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasound in primary care: a systematic review of generalist performed point-of-care ultrasound in unselected populations

Abstract: Background: Both the interest and actual extent of use of point-of-care ultrasound, PoCUS, among general practitioners or family physicians are increasing and training is also increasingly implemented in residency programs. However, the amount of research within the field is still rather limited compared to what is seen within other specialties in which it has become more established, such as in the specialty of emergency medicine. An assumption is made that what is relevant for emergency medicine physicians a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
109
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 204 publications
(226 reference statements)
1
109
0
4
Order By: Relevance
“…The study population was selected, and a LUS examination was only performed when clinical concerns about hospital referral appeared. Although several systematic reviews have suggested the usefulness of US in PC, [11][12][13][14] we are unaware of the existence of studies on LUS in PC (and specifically in COVID-19).…”
Section: Discussionmentioning
confidence: 99%
“…The study population was selected, and a LUS examination was only performed when clinical concerns about hospital referral appeared. Although several systematic reviews have suggested the usefulness of US in PC, [11][12][13][14] we are unaware of the existence of studies on LUS in PC (and specifically in COVID-19).…”
Section: Discussionmentioning
confidence: 99%
“…Dermatologic ultrasound, which is increasingly used in dermatology, has also improved diagnostic accuracy when combined with the clinical examination 3,4 . Point‐of‐care ultrasound is also increasingly used, and family physicians and general practitioners have found that it is cost‐effective, enhances their clinical diagnosis, and obviates specialist consultations 5 . Although teleultrasound is comparable to in‐person consultation in obstetrics 6 and cardiology, 7,8 it has not been tested as an effective diagnostic method in dermatology.…”
mentioning
confidence: 99%
“…3,4 Point-of-care ultrasound is also increasingly used, and family physicians and general practitioners have found that it is cost-effective, enhances their clinical diagnosis, and obviates specialist consultations. 5 Although teleultrasound is comparable to in-person consultation in obstetrics 6 and cardiology, 7,8 it has not been tested as an effective diagnostic method in dermatology. This study aimed to validate dermatologic ultrasound as a complementary tool in teledermatology.…”
mentioning
confidence: 99%
“…The ability of LUS to accurately diagnose pneumonia early in the course of the disease may improve outcomes for patients attending primary care. 43 Furthermore, improved diagnostic performance in patients with suspected CAP may reduce the need for antibiotics. On the other hand, the size of pulmonary lesions might be smaller in the early stages of disease and the results indicate that the usability of LUS to diagnose CAP is compromised by its inability to visualise pulmonary lesions that are not in contact with the pleura.…”
Section: Open Accessmentioning
confidence: 99%